A study on turbulence characteristics of a rectangular three-dimensional wall jet in a confined space using particle image velocimetry - Xingxing Zhang; Han Liu (PLoS ONE, 2026)
A three-dimensional wall jet in a confined space is a ubiquitous flow occurrence in important engineering domains. Previous studies have not fully explained its turbulence characteristics. In this paper, a particle image velocimetry measuring technique was used to observe a rectangular three-dimensional confined wall jet. The objective of this study is to investigate specially turbulence statistics in regions affected by the vertical wall (16 ≤ x/d < 27), and the effect of the Reynolds numbers and submerged depths on that. The results show that profiles of turbulence statistics are not similar in the region 16 ≤ x/d < 19. Turbulence characteristics in the region 19 ≤ x/d < 24 correspond to those of the radial decay region due to the influence of the vertical wall, where both the mean and fluctuating motions are completely developed in advance. In the region 24 ≤ x/d < 27, profiles of turbulence statistics in two planes collapse rather poorly. Peak values of turbulence quantities in the lateral plane show a positive correlation with Reynolds numbers obviously, while the similar trend is not presented in the symmetry plane. Furthermore, in the region 24 ≤ x/d < 27, profiles of turbulence intensities are little sensitive to small variations in submerged depths. However, peak values of Reynolds shear stresses show a positive correlation. This study can promote the understanding of turbulence characteristics of a three-dimensional confined wall jet.